Placenta accreta spectrum: a current literature review - Mohsen M. A. Abdelhafez; Karim A. M. Ahmed,; Mohd Nazri Bin Mohd Daud; Aya M. Eldiasty; Mohammad Saffree Jeffree; Fairrul Kadir; Dg Marshitah Pg Baharuddin; Win Win Than; Firdaus Hayati, DrGenSurg; Nornazirah bt.Azizan; Doreen Sumpat (SAGE Publications, 2023)
Objective: This literature review was designed to highlight the most up-to-date and evidence-based interventions, whenever available, regarding diagnostic imaging modalities and management strategies for patients, with the placenta accreta spectrum. Materials and Methods: A comprehensive review of the literature was conducted using database searches in Science Direct, Google Scholar, and PubMed to locate the most up-to-date information, related to this topic. Results: The placenta accreta spectrum has an unclear etiology, with cesarean delivery and placenta previa being the most implicated factors. Conclusion: There is a growing global consensus that the two main risk factors for placenta accreta are placenta previa and prior cesarean delivery. Up-to-date, grayscale sonography combined with Doppler interrogation is thought to be the best first-line assistance, for the identification of abnormal placental invasion. Cesarean hysterectomy, with placenta left in situ, is the classical surgical treatment.